CONSTRUCTION MEASURES REDUCE EXCESSIVE ACOUSTIC IMPACT ON RESIDENTIAL AREAS - Завьялов, Алексей; Машарский, Борис; Афанасьева, Татьяна; Копытенкова, Ольга (Modern engineering and innovative technologies, 2017)
The article presents the results of the study of the impact of rail vehicles on the environment and the effectiveness of materials used in the construction of acoustic screens to reduce the acoustic load on residential areas. Modern technical measuring in